Changes in Carotenoids and Quality Parameters of Sweet Paprika (Capsicum annuum) After an Accelerated Heat Treatment - Belén Olga Ferrando; Nieves Baenas; María Jesús Periago (Antioxidants)
Paprika, obtained from dried red pepper (C. annuum), is valued for its characteristic colour and flavour. Its carotenoid content, which is important for both sensory and nutritional quality, varies depending on several factors (agronomic conditions and technological treatment with special attention to the drying methods) that influence the colour and antioxidant capacity of the samples. This study investigated the effect of an accelerated thermal treatment (80 °C for 8 h) applied to evaluate the oxidative stability of the carotenoids and the colour of ground paprika depending on its origin (Peru or China). Changes in quality parameters (ASTA index and CIELAB colour), carotenoid content and profile (HPLC-DAD) and lipophilic antioxidant capacity (FRAP and ABTS•+ methods) were evaluated. Untreated Chinese samples had 30% more total carotenoids than Peruvian samples, but this was not reflected in ASTA units, indicating that at least a 50% carotenoid variation is required for significant differences. Treatment resulted in a carotenoid loss of 70% in Peruvian and 30% in Chinese samples, with changes in total carotenoids correlating positively with antioxidant capacity. Both origins had similar carotenoid profiles, with β-carotene being the predominant carotenoid, while distinct contents were observed between the origins. The higher content of esterified carotenoids in Chinese peppers resulted in better thermal stability. The results highlight the necessity for tailored production processes to maintain nutritional integrity and antioxidant capacity.